Prácticas pedagógicas para afianzar el desarrollo socioafectivo en niños de 5 a 6 años. - Jiménez Castillo, Mirka Lisseth (Machala, 2020)
The pedagogy consolidated in the socio-affective area determines that parents and teachers educate with love and dedication to the little ones, attending to their needs and providing them with tools that allow the acquisition of significant experiences for their evolutionary development; On the other hand, it should be emphasized that parents strengthen affective ties that are aroused in interpersonal interaction with infants from an early age, likewise it is essential to promote integral and welcoming environments that stimulate the interests of learning, expressing themselves and developing freely safely, trust and autonomy, which is why it is necessary to promote daily practices that strengthen education in values, habits and norms of coexistence. In a conclusive way, it is determined that pedagogical practices are fundamental in the teaching process, due to their contribution to the acquisition of knowledge and the personal, social and academic formation of the child; That is why the teacher as a counselor and guide, takes into consideration the evolutionary development of the child to adapt and use the appropriate strategies, methods and tools that facilitate the integral formation of the infant made up of areas of development, the socio-affective area being the most influential in the development of the infant for its potentializing contribution to identity, autonomy, and self-efficacy. Keywords: socio-affective development, pedagogical practices, teaching process, teacher, family, infant.
La pedagogía afianzada al área socioafectiva determina que los padres y maestros eduquen con amor y dedicación a los pequeños, atendiendo sus necesidades y brindándoles herramientas que permitan la adquisición de experiencias significativas para su desarrollo evolutivo; por otro lado, cabe recalcar que los padres, fortifican lazos afectivos que son suscitados en la interacción interpersonal con los infantes desde edades tempranas, así mismo es indispensable promover ambientes íntegros y acogedores que estimulen los intereses de aprender, expresarse y desenvolverse libremente con seguridad, confianza y autonomía, por lo cual es necesario que se fomente las prácticas cotidianas que afiancen la educación en valores, hábitos y normas de convivencia. De manera concluyente se determina que las prácticas pedagógicas son fundamentales en el proceso de enseñanza, por su contribución a la adquisición de conocimiento y a la formación personal, social y académica del niño; es por ello que el docente como orientador y guía, toma en consideración el desarrollo evolutivo del niño para adaptar y emplear las estrategias, métodos y herramientas adecuadas que facilitan la formación integral del infante conformado por áreas de desarrollo, siendo el área socio afectiva la más influyente en el desarrollo del infante por su aporte potencializador en la identidad, autonomía, y autoeficiencia.
Keywords: DESARROLLO SOCIOAFECTIVO; FAMILIA; DOCENTE